PENGARUH OPINI AUDIT DAN KUALITAS AUDITOR TERHADAP AUDIT DELAY PADA PEMERINTAH KABUPATEN/KOTA DI INDONESIA - Nila Aprila; Fachruzzaman Fachruzzaman; Desi Siska Pratiwi (Jurnal Akuntansi, 2017)
The purpose of this research is to examine the effect of audit opinion and auditor quality to audit delay on local government in Indonesia. Sampling method used is purposive sampling and the result are 419 local governments in fiscal year 2015. Research data taken from audited financial statements BPK. Method of data analysis using multiple linear regression. The audit opinion and auditor’s professional proficiency has siginificant negative effect on audit delay. And auditor’s accounting educational background has not effect on audit delay.Keywords : audit delay, audit opinion, auditor quality